Variation in the Immunoregulatory and Antiviral Cytokine mRNA Levels between Lentogenic and Velogenic Pathotypes of Avian Orthoavulavirus-1 - Rajasekaran, Ranjani; John, John Kirubaharan; Chandran , N Daniel Joy (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Future strategies to control Avian Orthoavulavirus-1 (AOaV-1), the causative agent of Newcastle disease (ND) in poultry, would  rely extensively on virus-host interactions. Cytokines, the molecular messengers of immune system, are considered a significant  entity in understanding the complex interplay between virus and host immune response. In the present study, the mRNA levels of  immunoregulatory (IFN-γ and IL-12) and antiviral (IFN-α and IFN-β) cytokines were studied in in-vitro (chicken embryo fibroblast cells -  CEF) and in-vivo (spleen of chicken) systems in response to lentogenic (D58) and viscerotropic velogenic (D165) AOaV-1 at five time points  after experimental infection (1, 2, 3, 4 and 5 days post-infection). The mRNA levels of immunoregulatory and antiviral cytokines varied  significantly between lentogenic D58 and velogenic D165 across both the systems at all time points under study. It was significantly  upregulated for velogenic D165 when compared to lentogenic D58. This significant difference indicated that induction of cytokinesis  unique for different pathotypes of AOaV-1, thereby highlighting the importance of studying cytokine mRNA levels to understand  molecular pathogenesis of AOaV-1.
Keywords: Newcastle Disease Virus; Immune response; lentogenic pathotype; velogenic pathotype; cytokine mRNA level; immunoregulatory cytokine; antiviral cytokine